Speckle in polarization structured light. Issue 1 (2nd January 2022) - Kumar, Basant; Lochab, Priyanka; Baidya Kayal, Esha; Ghai, Devinder P.; Senthilkumaran, P.; Khare, Kedar
Abstract : We show that the far-field speckle patterns observed on the transmission of polarization structured light beams through a random diffuser screen have distinct spatial textures, which significantly differ from the texture of the fully developed scalar speckle. In particular, we report on speckle observed using the V-point and C-point polarization singular beams for illumination in this work. The V-point and C-point polarization singularities are generated by a combination of different orbital angular momentum (OAM) states in orthogonal polarizations. When passed through a random diffuser screen, the on-axis far-field diffraction intensity is an incoherent summation of speckle intensities due to the individual OAM states. Unlike the typical grainy structure in the scalar speckle, the speckle patterns observed with V-point and C-point illuminating beams are seen to have a noodle-like and sponge-like textures respectively. The speckle from V-point and C-point illuminations is difficult to distinguish using the usual intensity statistics which does not account for the distinct spatial structure of the speckle patterns. The Gray Level Co-occurrence Matrix (GLCM) methodology was therefore used to extract a number of spatial textural features from the speckle patterns observed using scalar and polarization structured illuminations. The principal component analysis (PCA) technique when applied to the texture parameters shows that it is possible to identify the nature of the illuminating beam by simply observing the texture properties of the resultant speckle pattern. When coherent light beams pass through a random medium resulting in a fully developed speckle pattern, the information regarding the profile of the input beam is generally considered to be lost. Our new observations on distinct textural features in speckle from structured light therefore suggest the possibility of information transmission through random media by means of switching the polarization structure of the incident beam.